2001
DOI: 10.1073/pnas.201360898
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of forkhead box M1B transcription factor in transgenic mouse hepatocytes prevent age-related proliferation defects in regenerating liver

Abstract: The forkhead box (Fox) family of transcription factors share homology in the winged helix͞forkhead DNA-binding domain and play important roles in regulating cellular proliferation, differentiation, longevity, and cellular transformation. Forkhead box M1B (FoxM1B) is a ubiquitously expressed member of the Fox transcription factor family whose expression is restricted to proliferating cells and that mediates hepatocyte entry into DNA synthesis and mitosis during liver regeneration. Recent cDNA microarray studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
218
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(239 citation statements)
references
References 37 publications
20
218
0
1
Order By: Relevance
“…These results suggest that Foxm1 may regulate other genes essential for cardiomyocyte entry into mitosis during heart morphogenesis. In this study, we found that Foxm1 Ϫ/Ϫ hearts display reduced expression of Cdc25B phosphatase, a result consistent with diminished levels of Cdc25B in proliferating Foxm1 Ϫ/Ϫ hepatocytes following a partial hepatoctomy (Wang et al, 2001). In addition, increased nuclear levels of Cdk inhibitor p21 may not only prevent activation of Cdk2, but p21 can also complex with and inhibit activity of M-phase promoting Cdk1 protein (Op De Beeck et al, 2001;Patel et al, 2002;Dash and El-Deiry, 2005).…”
Section: Foxm1 Is Essential For Heart Development 1007supporting
confidence: 77%
See 2 more Smart Citations
“…These results suggest that Foxm1 may regulate other genes essential for cardiomyocyte entry into mitosis during heart morphogenesis. In this study, we found that Foxm1 Ϫ/Ϫ hearts display reduced expression of Cdc25B phosphatase, a result consistent with diminished levels of Cdc25B in proliferating Foxm1 Ϫ/Ϫ hepatocytes following a partial hepatoctomy (Wang et al, 2001). In addition, increased nuclear levels of Cdk inhibitor p21 may not only prevent activation of Cdk2, but p21 can also complex with and inhibit activity of M-phase promoting Cdk1 protein (Op De Beeck et al, 2001;Patel et al, 2002;Dash and El-Deiry, 2005).…”
Section: Foxm1 Is Essential For Heart Development 1007supporting
confidence: 77%
“…3I), we observed an 80% reduction in the expression of Cdc25B phosphatase (Fig. 4), a known transcriptional target for Foxm1 protein (Wang et al, 2001). Because Cdc25B is essential for activation of Cdk1/ cyclin B complex during M-phase progression (Borgne and Meijer, 1996), diminished Cdc25B levels may cause delayed cardiomyocyte entry into mitosis in Foxm1 Ϫ/Ϫ hearts, causing polyploid phenotype.…”
Section: Gene Expression Profile In Foxm1 ؊/؊ Heartmentioning
confidence: 74%
See 1 more Smart Citation
“…According to previous results (Bucher et al 1964;Fry et al 1984;Wang et al 2001), while a strong proliferative response, as detected by BrdU incorporation, was observed in young mice (Fig. 2a, b), (LI of 52.5 %±8.8), liver regeneration was severely impaired in old mice; indeed, virtually, no hepatocyte nuclei were BrdU-positive at the same time point (LI of 1.5 %±0.5).…”
Section: Resultssupporting
confidence: 74%
“…Indeed, while in young rats, DNA synthesis peaks at 24 h after PH, in old animals, the S phase peak is reached at 36 h. Different explanation has been proposed to justify this proliferation defect observed in aged rodents. Among these, Wang et al (2001) showed that aging process is associated with reduced expression of the cell cycle gene Forkhead Box M1 (Foxm1). Foxm1 has been suggested to be essential in regulating expression of genes involved in cell proliferation since increased levels of this transcription factor stimulate expression of cyclin D1, A2, B1, and B2 and are sufficient to restore cell cycle by promoting gene expression and to potentiate hepatocyte proliferation in aged mice.…”
Section: Introductionmentioning
confidence: 99%